Data Structures & Algorithms in Java - Lafore, Robert (Noida, India Pearson Education, 2017)
Algorithms are the procedures that software programs use to manipulate data structures. Besides clear and simple example programs, this work includes a workshop as a small demonstration program executable on a Web browser. The programs demonstrate in graphical form what data structures look like and how they operate
Include Appendix and Index
Keywords: Java (Computer program language) -- Computer algorithms -- Data structures (Computer science)